The bamboo delignification saturation point in alkaline hydrogen peroxide pretreatment and its association with enzymatic hydrolysis. (September 2022) - Huang, Chen; Zhan, Yunni; Cheng, Jinyuan; Wang, Jia; Meng, Xianzhi; Fang, Guigan; Ragauskas, Arthur J.
Graphic abstract: Highlights: A delignification saturation point (DSP) was reported in bamboo AHP pretreatment. DSP has strong association with the enzymatic hydrolysis. The undegradable lignin mainly exists in the cell corner of SF. Residual lignins at different H2 O2 dosages have similar chemical structure. Abstract: A delignification saturation point (DSP) was observed for bamboo alkaline hydrogen peroxide pretreatment (AHP). Lignin removal was increased from 52.23% to ∼70% when increasing H2 O2 dosage from 0% to 2% at the optimum pH, but it cannot be further reinforced as increasing the H2 O2 . With partial lignin preserved, the glucan hydrolysis yield was found to have a ceiling of ∼80%. This study indicated a strong association between enzymatic digestibility and lignin removal. Anatomical analysis by fluorescence microscope and confocal Raman microscope revealed that the undegradable lignin was mainly existing in the cell corner of sclerenchyma fibers, causing the DSP in the bamboo AHP. Finally, the residual lignin in pretreated bamboo was characterized with GPC, HSQC NMR, and 31 P NMR, which revealed the nature of DSP. This study could help to understand the lignin modification during the AHP and further contribute to the establishment of a chemical-saving biorefinery.